European neutrals and non-belligerents during the Second World War - Wylie, Neville 1966- (Cambridge University Press, 2002)
This collection provides a comprehensive English-language survey of the conduct of neutral and non-belligerent states during the war. Instead of narrowly focusing on the few neutrals that survived the war intact, the volume broadens our understanding of neutrality, by including chapters on 'non-belligerents' and those neutrals of south-east Europe, such as Romania and Yugoslavia. The essays focus on how individual neutral governments perceived international developments and throw light on the domestic political circumstances that critically affected their response to the course of the war. They therefore provide the political context that has been overlooked in controversies surrounding their humanitarian and financial activities. While based on the authors' own research, the essays draw widely on secondary literature and provide invaluable analytical introductions to the large amount of historical writing on these countries